Epidemiological investigation of grass seed foreign body‐related disease in dogs of the Riverina District of rural Australia. Issue 3 (March 2016) - Hicks, A; Golland, D; Heller, J; Malik, R; Combs, M
Abstract : Objective: To characterise disease presentations caused by grass seed foreign body‐related disease (GSFBD) in dogs, identify predisposing risk factors and suggest effective prevention strategies. Methods: A retrospective, case–control, telephone survey was conducted to obtain information on GSFBD in dogs from the Riverina district of New South Wales (NSW). Additionally, retrospective case records were obtained from Wagga Wagga Veterinary Hospital and Charles Sturt University Veterinary Teaching Hospital over the period July 2006 to October 2011. Signalment, history, investigative strategies, location and severity of lesion(s), cost of therapy, length of hospitalisation, recurrence rate and microbiology data were recorded. Results: Cases (473 dogs) meeting stringent inclusion criteria were identified. GSFBD comprised 2.0% of hospital presentations. Breeds with high‐density coats were overrepresented. Otitis externa was the most common manifestation of GSFBD in the general practice (47%). In the referral practice pyothorax was the most common entity (34%). In both practices the range of clinical manifestations was broad, including a small number of dogs with catastrophic intracranial disease. Univariable and multivariable logistic regression analyses demonstrated dogs with GSFBD had 3‐fold greater odds of having medium coats than short coats and 5‐fold less odds of being groomed. Conclusions and clinical relevance: Grass seeds are a major cause of disease in the dogs of south‐west rural NSW, with presentations ranging from mild lameness to severe neurological disease. Some protection from GSFBD was achieved with frequent grooming. Clipping or coat searching without grooming was ineffective as a prevention strategy.